2021
DOI: 10.1038/s41598-021-86914-8
|View full text |Cite|
|
Sign up to set email alerts
|

Network pharmacology and molecular docking study on the active ingredients of qidengmingmu capsule for the treatment of diabetic retinopathy

Abstract: Diabetic retinopathy (DR) is a leading cause of irreversible blindness globally. Qidengmingmu Capsule (QC) is a Chinese patent medicine used to treat DR, but the molecular mechanism of the treatment remains unknown. In this study, we identified and validated potential molecular mechanisms involved in the treatment of DR with QC via network pharmacology and molecular docking methods. The results of Ingredient-DR Target Network showed that 134 common targets and 20 active ingredients of QC were involved. Accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…The 3D structures of food-derived compounds and initial complex structures for MD simulations are displayed in Figures 1 and 2. Molecular docking was conducted to provide initial models of the complex systems for subsequent MD simulation studies [34]. The X-ray crystal structure of the PD-L1 dimer (PDB ID 5N2F) was used as the receptor for this study.…”
Section: Dockingmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D structures of food-derived compounds and initial complex structures for MD simulations are displayed in Figures 1 and 2. Molecular docking was conducted to provide initial models of the complex systems for subsequent MD simulation studies [34]. The X-ray crystal structure of the PD-L1 dimer (PDB ID 5N2F) was used as the receptor for this study.…”
Section: Dockingmentioning
confidence: 99%
“…Molecular docking is a tool for predicting ligands' binding affinities to target proteins and exploring their possible binding modes [34]. The crystal structures of the PD-L1 dimer (PDB ID: 5N2F), CC (PDB ID: 4K58), RSV (PDB ID: 1CGZ) and EGCG (PDB ID: 3NG5) were acquired from the Protein Data Bank (PDB) database.…”
Section: Molecular Dockingmentioning
confidence: 99%
“…It is worth mentioning that, celastrol plays a role in inhibiting PI3K/AKT signaling pathway in the treatment of various diseases, such as glioblastoma and prostate cancer ( Pang et al, 2010 ; Kannaiyan et al, 2011 ). Besides, it is thought to be correlated with the cell cycle ( Zhang M. et al, 2021 ). Li H et al reported that PTEN, a negative regulating factor, may suppress the PI3K/AKT pathway and maintain moderate T cell proliferation in healthy individuals ( Li et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The species was then set to Homo sapience and the minimum required interaction score to the highest confidence of 0.9 in order to retrieve the concise protein–protein interaction (PPI) information for the next step of the analysis. The PPI network was also visualized with Cytoscape software [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The results of the KEGG enrichment analysis were used to construct a KEGG pathway network to determine the proteins involved in the treatment effects of HC. Based on the STRING results, the gene–pathway of HC against pneumonia was constructed to delineate the various pathways and key targets in order to explore the potential mechanisms underlying the effect of HC on the treatment of pneumonia [ 28 ].…”
Section: Methodsmentioning
confidence: 99%